Factors in determining store loyalty among consumers in Malacca City / Gloria Ann Anin and Yusmanizza Marlinny Usop - Anin, Gloria Ann; Usop, Yusmanizza Marlinny (Faculty of Business and Management, 2014)
This study is conducted as a partial fulfilment of the coursework of Industrial Training Project Paper (MKT 669). The title of this study is “Factors in Determining Store Loyalty among Consumers in Malacca City”. The main objectives of this study are to assess the current level of customer’s loyalty toward the stores in Malacca City, to identify the most influential factor that influencing the store’s loyalty among consumers and to find out the significant relationship between store loyalty and service quality, sales promotion, store image, and physical evidence. This study was conducted around Malacca City district covers on the supermarket and hypermarket products. Through this study, it will provide retailers with useful information about Malacca City customers store loyalty determinants. Study results should be useful for retailers in Malaysia generally and especially Malacca City grocery market when developing marketing strategies, when considering how retailer‘s best can position their stores and which store loyalty determinants marketer needs to improve, in order to maintain customer loyalty.